2016
DOI: 10.1016/j.joen.2016.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Collagen-Apatite Nanocomposites for Bone Regeneration

Abstract: The present study lays the foundation for the development of Col-Ap nanocomposite-based bone grafts for future clinical applications in bone regeneration of large periapical lesions after apical curettage or apicoectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…In this study, we first reported the use of biomimetic IMC in combination with autologous PDLSCs for the regeneration of large bone defects in minipigs. Compared with rat critical-sized mandibular defects of approximately 5 mm in diameter in our previous studies 27 , 28 , the defect area of approximately 2 cm width × 3 cm length × 0.5 cm depth) in this study is an order of magnitude greater. The IMC still possesses an excellent bone regeneration and vascularization potential.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In this study, we first reported the use of biomimetic IMC in combination with autologous PDLSCs for the regeneration of large bone defects in minipigs. Compared with rat critical-sized mandibular defects of approximately 5 mm in diameter in our previous studies 27 , 28 , the defect area of approximately 2 cm width × 3 cm length × 0.5 cm depth) in this study is an order of magnitude greater. The IMC still possesses an excellent bone regeneration and vascularization potential.…”
Section: Discussioncontrasting
confidence: 55%
“…The 3-D macroporous IMC scaffold was prepared using a modified bottom-up biomimetic approach 27 , 28 . Briefly, type I tropocollagen solution (Corning, 10 mg/mL, pH < 2) was slowly injected into a dialysis flask (3500 Da), which was immersed in a mineralization solution (pH = 7.4) containing poly(acrylic acid) (0.25 mM, Mw 2000, Sigma-Aldrich), type I white Portland cement (0.2 g/mL, Lehigh Cement Co.) and simulated body fluid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Col-Ap nanocomposite scaffold was able to activate boneforming cells, promote inward vascularization, as well as induce the synthesis of the ECM mediated by increased TGFb1. (Liu et al, 2016). In addition, Haj et al demonstrated that nanofibrous HA/chitosan (nHAp/CTS) scaffolds seeded with MSCs were superior to membranous HAp/CTS in a rat FIGURE 1 | Schematic preparation of ECM-based scaffold in bone regeneration.…”
Section: Ecm-modified Biomaterials Scaffoldmentioning
confidence: 99%
“…The use of antimicrobial agents for the chemomechanical preparation of infected root canals, followed by obturation and coronal repair, provides beneficial results. However, sometimes infective microorganisms that reside in the root canals may gradually gain multiple resistance to drugs or disinfection methods, and this would eventually lead to the failure of root canal treatment [ 1 , 2 ] and more severe problems, such as chronic apical periodontitis and local bone resorption [ 3 ]. In such cases, endodontic surgery is commonly required to eradicate these microorganisms, and such surgical procedures usually include the mechanical removal of part of the infected tooth, followed by irrigation of antibacterial agents into the cavity before manual filling of cavities with impermeable body fluids, which have the ability to adhere to dentinal walls [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%